2002
DOI: 10.1002/mus.10146
|View full text |Cite
|
Sign up to set email alerts
|

Macroelectromyography: A review of the technique and its value in the investigation of neuromuscular disorders

Abstract: The background for the macroelectromyography technique, which was developed by Erik Stålberg to measure the size of motor unit potentials in human muscles, is reviewed. The method employs a modified single-fiber electrode with a large nonselective recording surface capable of recording the activity from all the fibers of a motor unit. The findings in normal subjects and its application in the study of motor unit recruitment are described. The value of the technique in the investigation, diagnosis, and monitori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The amplitude of the macro‐MUP is directly related to the number of the muscle fibers within the MU 1. The FD gives a measure of the focal distribution of the muscle fibers in the motor unit 6…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The amplitude of the macro‐MUP is directly related to the number of the muscle fibers within the MU 1. The FD gives a measure of the focal distribution of the muscle fibers in the motor unit 6…”
Section: Discussionmentioning
confidence: 99%
“…Macro electromyography (EMG) studies in humans have confirmed that MUs with larger electrical size are recruited at higher force output 3. The amplitude of the macro‐motor unit potential (macro‐MUP) is directly related to the number of muscle fibers within the MU 1. Thus, the large, high recruitment threshold macro‐MUPs could be generated by MUs with either higher muscle fiber density (FD) or larger territory.…”
mentioning
confidence: 99%
“…The amplitude and area of the macro‐MUP is typically increased (Fig. 6C) in conditions of reinnervation such as polyneuropathies and mononeuropathies 2. Consequently, the amplitude of the macro‐MUP is an indicator of the degree of denervation and of the reinnervation capacity of the surviving motor neurons.…”
Section: Macro Electromyography In Neuromuscular Disordersmentioning
confidence: 98%
“… Abstract The macro electromyography method was developed in the 1980s 1. Since then, technical modifications have been made, and a number of conditions have been explored 2, 3. This study is a methodological introduction and an update of findings in some nerve–muscle disorders.…”
mentioning
confidence: 99%